The Role of Leadership and Leaders’ Behavioral Characteristic on Employees: A Study of Petronas Berhad - Muhammad Aiman Bin Mohd Farid; Daisy Mui Hung Kee; Muhammad Saifulhaq Bin Mohamad; Muhammad Sharizul Ukasha Bin Hameem; Ahmad Zulfahmi Bin Zulkafli (International Journal of Applied Business and International Management, 2020)
Petronas Chemical Group is one of the largest and most popular companies in Southern Asia primarily involved in marketing, manufacturing, and selling diversified ranges of chemical products. The main purpose of this research paper is to determine the role of leaderships and leaders’ behavioral characteristic on employees of Petronas Chemical Group. This study focuses on types of leadership its leaders assert in the working environment to sustain the development of their employees’ performance. This study may strengthen the understanding of the role of leadership or leadership style that will chip in employee job performance.